TEACHING READING BY USING VERBAL FOOTBALL GAME TO THE EIGHTH GRADE STUDENTS OF IGNATIUS JUNIOR HIGH SCHOOL OF PALEMBANG - Ermala Sari (Universitas PGRI Palembang, 2019)
Abstract: The main problem of this research wasâ€ Is it effective to teach reading by using verbal football game to the eighth grade students of Ignatius Junior High School Palembang?â€. The objective of this research is to find out whether or not it is effective to teach reading by using verbal football game to the eighth grade students of Ignatius Junior High School Palembang. This research used pre-experimental design. The population of this research was taken from the whole of the eighth grade students of Ignatius Junior High School Palembang in the academic year of 2017/2018 with the total number of students was 61 students. The sample was class VIII.1. There were 30 students being selected by using convenience non random sampling. The data were collected by using written test with the total numbers of questions were forty (40) questions in the form of multiple choice items and analyzed by using matched t-test calculation. Â The result of the research showed that there was progress in studentsâ€™ reading skill and achievement. The findings showed that there was a significant difference between the pre-test and post-test results,Â the average scoreÂ in the pre-test was 5.11 while in the post-test was 7.88 with Î± = 0.05 and df = 29 the critical value of t was 1.697. From the result of matched t-test calculation, it was found that the value ofÂ t-obtained was 13.83.Â The result of matched t-test calculation proved that t-obtained (11.54) is higher than t-critical (1.697). It indicated that the alternative hyporesearch (Ha) was accepted and null hyporesearch (Ho) was rejected.Keywords: Teaching, Reading, Football, Games